Seção Técnica de Finanças - Carvalho, Antonio Carlos de; Pulli, Tânia Mara Sunega; Santos, Viviane Pagani Lopes dos (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação Tânia Mara Sunega Pulli Viviane Pagani Lopes dos Santos